Efficacy of photodynamic therapy in the treatment of port wine stains: A systematic review and meta-analysis - Wang, Ling; Li, Lei; Huang, Chao (Frontiers in Medicine, 2023)
Background: Port wine stains (PWS) often cause cosmetic effects and psychological distress. Pulsed dye lasers (PDL) and photodynamic therapy (PDT) are the most commonly used treatments. PDL is still the “gold standard” of therapy to date. However, its shortcomings have become apparent as clinical applications have increased. PDT has been proven as an alternative to PDL. Patients with PWS still lack enough evidence about PDT to make informed treatment decisions. Objective: The purpose of this systematic review and meta-analysis was to assess the safety and effectiveness of PDT for PWS. Methods: The online datasets, comprising PubMed, Embase, Web of Science, and the Cochrane Library, were searched for meta-analysis-relevant publications. Two reviewers separately evaluated the risk of bias in each listed study. Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was used to assess the treatment and safety outcomes. Results: Our search retrieved 740 hits and only 26 studies were finally included. Among the 26 studies included, 3 were randomized clinical trials, and 23 were prospective or retrospective cohort investigations. Based on a gathered assessment, the percentage of individuals achieving a 60% improvement was estimated to be 51.5% (95% confidence interval (CI): 38.7–64.1; I2 = 83.8%) and a ≥75% improvement was 20.5% (95% CI: 14.5–26.5; I2 = 78.2%) after 1 to 8.2 treatment sessions (GRADE score: very low). Due to the statistical diversity of the meta-analysis, a subgroup assessment was performed to determine the sources of diversity. The collected findings indicated that the impact of PDT on enhancing the medical effectiveness of PWS was significant in different treatment sessions, different types of ages, different locations of PWS, and different types of PWS. Pain and edema occurred in most patients. Hyperpigmentation was present in 7.9–34.1% of the patients in 17 studies. Photosensitive dermatitis, hypopigmentation, blister, and scar were infrequently reported, with 0%–5.8% incidences. Conclusions: PDT is recommended as a safe and effective treatment for PWS based on the current evidence. However, our findings are based on poor-quality evidence. Therefore, comparative investigations of a large scale and high quality are necessary to support this conclusion.